THE GENOTYPES X ENVIRONMENT INTERACTION FOR STARCH YIELD IN NINE-MONTH OLD CASSAVA PROMISING CLONES - Sholihin Sholihin (Indonesian Journal of Agricultural Science, 2009)
Cassava (Manihot esculenta) is planted in dry areas with different environmental conditions, therefore the yield is varied. The aim of the study was to analyze the genotype x environment interaction for starch yield in 9-month old cassava promising clones. The experiment was conducted on mineral soils in four different locations, i.e. Lumajang-East Java (Inceptisols), Kediri-East Java (Entisols), Pati-Central Java (Alfisols), and Tulangbawang-Lampung (Ultisols) during 2004- 2005. The experiment was arranged in split plot design with three replications. The main plots were cultivation techniques, i.e. simple technology and improved technology, whereas the subplots were 15 cassava promising clones. Starch yield of 9- month old cassava plants was analysed using the additive maineffects and multiplicative interaction (AMMI). The results showed that environmental factors determined the stability of starch yield were soil bulk density on subsoil, the number of rainy days at fifth month, minimum air temperature at fourth month, and minimum air humidity at seventh month. CMM97002-183, Adira 4, CMM97007-145, CMM97007-235, Malang 2, CMM97002-36, and CMM97006-44 were identified as the stable cassava clones for starch yield in 9-month old. Average starch yield of Adira 4 was the third after MLG 10311 and CMM 97006-52. The CMM97006-52 was adapted to the soils having high P2O5 content on topsoil, high minimum air temperature at 4 and 5 months after planting, high minimum relative humidity at 7 months after planting, low total rainfall at 5 months after planting, and low number of rainy days at 5 and 8 months after planting. MLG 10311 was adapted to low soil bulk density. The average starch yield of MLG 10311 was the highest at 9 months after planting. The study implies that advanced trials for CMM 977006-52 and MLG 10311 clones are needed, so the clones can be released as new varieties of cassava. In selection and evaluation, the bulk density on subsoil is needed to be attained specifically to increase the probability to obtain new variety of cassava.